2020
DOI: 10.3390/ma13040954
|View full text |Cite
|
Sign up to set email alerts
|

Waste-to-Carbon: Is the Torrefied Sewage Sludge with High Ash Content a Better Fuel or Fertilizer?

Abstract: Sewage sludge (SS) recycling is an important part of the proposed ‘circular economy’ concept. SS can be valorized via torrefaction (also known as ‘low-temperature pyrolysis’ or ‘roasting’). SS can, therefore, be considered a low-quality fuel or a source of nutrients essential for plant growth. Biochar produced by torrefaction of SS is a form of carbonized fuel or fertilizer. In this research, for the first time, we tested the feasibility of torrefaction of SS with high ash content for either fuel or organic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
(92 reference statements)
2
18
0
Order By: Relevance
“…Biochar applications in crop agriculture are often limited by the heavy metals content associated with some types of feedstock and sources (Pulka et al, 2020). Biochar is capable of sorbing heavy metals and making them less available to soil exchange sites for the plant to uptake (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Biochar applications in crop agriculture are often limited by the heavy metals content associated with some types of feedstock and sources (Pulka et al, 2020). Biochar is capable of sorbing heavy metals and making them less available to soil exchange sites for the plant to uptake (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Data presenting the fuel properties of SS and biochars (lost on the ignition, ash content, C, H, N, O, higher heating value, lower heating values) and fertilizer properties of SS and biochars (Ca, Mg, K, Na content) obtained in this experiment were published by [6]. Raw data of solid content, mass yield, HM contents in SS and biochars, hydrophobicity, toxicity, and HMs' and other pollutants' concentrations in water extracts from SS and biochars are included as Supplementary Materials Excel S1.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Biochar is generated from the thermal treatment (torrefaction, pyrolysis) of biowaste [1]. Recent studies indicated that sewage sludge (SS) is a suitable feedstock for torrefaction [2][3][4][5][6]. Torrefaction (also known as "roasting" or "high-temperature drying") could densify carbon and stabilize SS, thereby offering a sustainable resource recovery solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations